Photo-oxidation of polyphenylenevinylene chains in Langmuir-Blodgett and cast films - Ferreira, Marystela [UNESP]; Olivati, Clarissa A. [UNESP]; Balogh, Débora T. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Poly(p-phenylene vinylene) (PPV) derivatives are well known for their applications in polymer light emitting diodes (PLEDs). These derivatives are highly susceptible to photooxidation though, which is mainly caused by the scission of the vinyl double bond on the polymer backbone. In this work, we show that Langmuir-Blodgett (LB) films are less degraded than cast films of a PPV derivative (OC1OC6-PPV). Both films had similar thickness (∼50 nm) to allow for a more realistic comparison. Photodegradation experiments were carried out by illuminating the films with white light from a halogen lamp (50W, 12 V), placed at a fixed dstance from the sample. The decay was monitored by UV-Vis and FTIR spectroscopies. The results showed that cast films are completely degraded in ca. 300 min, while LB took longer times, ca. 1000 min, i.e. 3 times the values for the cast films. The degradation process occurs in at least two stages, the rates of which were calculated assuming that the reaction follows a first order kinetics. The characteristic times for the first stage were 3.6×10-2 and 1.3×10-3 min-1 for cast and LB films, respectively. For the second stage the characteristic times were 5.6×10-2 and 5.0×10 -3 min-1. The differences can be attributed to the more compact morphology in the LB than in the cast films. With a compact morphology the diffusion of oxygen in the LB film is hampered and this causes a delay in the degradation process.
Keywords: Chemical bonds; Derivatives; Film thickness; Organic light emitting diodes (OLED); Photodegradation; Photooxidation; Polymer films; Cast films; Halogen lamps; Polymer backbone; Polyphenylenevinylene; Langmuir Blodgett films